Explant rates of electrical neuromodulation devices in 1177 patients in a single center over an 11-year period. Issue 11 (26th August 2020) - Al-Kaisy, Adnan; Royds, Jonathan; Al-Kaisy, Omar; Palmisani, Stefano; Pang, David; Smith, Tom; Padfield, Nicholas; Harris, Stephany; Wesley, Samuel; Yearwood, Thomas Lamar; Ward, Stephen
Abstract : Introduction: The publication of explant rates has established risk factors and a definitive objective outcome of failure for spinal cord stimulation (SCS) treating neuropathic pain. We present a UK study analyzing explants of electrical neuromodulation devices for different conditions over 11 years in a single center specializing in neuromodulation. Methods: A retrospective analysis was performed using a departmental database between 2008 and 2019. Explants were analyzed according to condition, mode of stimulation and other demographics using logistic regression and Kaplan-Meier graphs with log-rank (Mantel-Cox) test. Results: Out of a total of 1177 patients, the explant rate was 17.8% at 5 years and 25.2% at 10 years. Loss of efficacy was the most frequent reason for explant 119/181 (65%). Multivariant regression analysis indicated patients with back pain without prior surgery had a reduced risk of explant (p=0.03). Patients with SCS systems that had 10 kHz, options of multiple waveforms, and rechargeable batteries also had a decreased risk of explant (p<0.001). None of these findings were confirmed when comparing Kaplan-Meier graphs, however. Contrary to other studies, we found gender and age were not independent variables for explant. Conclusion: These data contribute to a growing list of explant data in the scientific literature and give indications of what factors contribute to long-term utilization of electrical neuromodulation devices.